Reliability and Validity of the Utrecht Tasks for Attention in Toddlers Using Eye Tracking (UTATE) - van Baar, Anneloes L.; de Jong, Marjanneke; Maat, Martine; Hooge, Ignace T. C.; Bogičević, Lilly; Verhoeven, Marjolein (Frontiers in Psychology, 2020)
Attention problems hinder many children in their cognitive and social emotional development. Children at risk for developmental problems, like preterm born infants, are specifically known for attention difficulties. Early identification of attention difficulties is important for application of appropriate stimulation in trying to reduce further problems. Specifically designed instruments with good psychometric characteristics are needed to show difficulties in attention, that may contribute to early identification. The Utrecht Tasks of Attention in Toddlers using Eye tracking (UTATE) is an instrument to measure orienting, alerting and executive attention capacities in young children. Reliability and validity of the UTATE are specifically addressed in three studies, reported in this paper. A sample of 95 term born children assessed at 18 months of age was used that provided data for both the second and third study reported here. , next toIn addition, three other small samples were used, of which the first consisted of 12 children at 18 months with test-retest data available that are reported in the first study,. the second Two other samples consisted of 14 children measured at 12 months, and the third of 15 children examined at 24 months. The UTATE resulted in reliable information on eye movements and some first support for construct and predictive validity was found. Low scores on the UTATE at 18 months were found to be related to slower cognitive development as measured with the Bayley-III-NL at 24 months. Furthermore, a first indication that the UTATE is able to detect some age differences in attention was foundshown. It is concluded that the UTATE can be used to study attention capacities in toddlers that underlie cognitive functioning and development, but further research is necessary.